PEMBELAJARAN BERBASIS BERPIKIR KRITIS DAN KREATIF - Yurniwati Yurniwati (Perspektif Ilmu Pendidikan, 2006)
In this 20 th century education is demanded to be able to in counter all changes and development in all aspect of life. The advancement of technology which develops very fast as encourages the development of science and technology. To anticipate and face all kinds of development, the teachers should prepare the children to follow the development of sciences and technology. Now days the students should receive all information from the teachers critically. They also expected to be involve mentally in constructing knowledge. One of the tools to enable the student to construct knowledge is ability to think critically and creatively revering to the research conducted by ALPS therefore approaches that can be taken to train ability to think critically and creatively. They are thinking thematic thinking, disposotioning thinking, transfering thinking, and assesing thinking.